Improving work‐life balance for ATs can reduce school's risk, liability. Issue 11 (23rd February 2018) - Neal, Timothy
Abstract : Athletic training in the college athletics setting has its challenges. Given the amount and year‐round nature of activities the athletic trainer is expected to cover, combined with team travel; meetings with coaches, staff, administrators, and recruits; and texts and emails coming in at all hours from coaches and student‐athletes, ATs have little time off. Add in the pressure of providing health care to a population expecting quick results to maintain their rigorous training, practicing, and seasonal competition (traditional and nontraditional season), plus the potential for litigation with every decision, ATs are set up for burnout, mistakes, and attitude challenges. ATs miss family functions, holidays, semester breaks, opportunities for professional development and continuing education, and summer vacations due to workload expectations. Athletics departments should pay attention to the red flag of concern raised by the potential liability that can result from overworked, under‐paid ATs trying to keep up with 80‐plus‐hour workweeks.